Effect of cocoa pod husk-based compost and watering frequencies on Phytophthora seedling blight disease suppression and seedling growth of cocoa clones - Bruce, Williams (Acta agriculturae Slovenica, 2025)
Phytophthora Seedling Blight Disease (PSBD) is a significant threat to global cacao production, causing stem and leaf wilting, defoliation, and seedling death within seven days of infection. The persistence of Phytophthora palmivora Butler in soil as mycelia and spores complicates its management. Composting, particularly with cocoa pod husks, enriches soil and suppresses plant diseases. Cocoa pod husk compost enhances seedling growth, improving plant height, dry matter, and foliar nitrogen. Cocoa pod husks also present a sustainable substratum for composting, as a substantial amount of it is left unused after bean harvesting. This study investigated the effects of cocoa pod husk-based compost and watering frequencies on PSBD suppression and cocoa seedling performance. Con-ducted in Prestea Nkwanta, Ghana, the experiment involved three factors: cocoa hybrid genotypes (PA150 and C85), compost ratios (soil alone, compost alone, 9 kg compost + 81 kg soil, and 18 kg compost + 72 kg soil), and watering frequencies (twice or thrice weekly). Disease incidence, growth, and root architecture parameters were analyzed using GenStat. Results showed significantly higher PSBD incidence in soil alone compared to compost-amended soils (p < 0.05). Growth parameters also varied significantly among treatments (p < 0.05). Cocoa pod husk compost significantly improved cocoa growth and suppressed PSBD, with reduced watering frequency enhancing effectiveness.
Keywords: arhitektura korenin; cocoa hybrid genotypes; cocoa pod husk compost; cocoa seedling growth; disease suppression; dodatki k prsti; hibridni genotipi kakavovca; kompost iz plodov kakavovca; rast sejank kakavovca; root architecture; soil amendment; zatiranje bolezni